Analysis of Online Shopping Choice through Shopping Experience and Ease of Transactions on Consumer Trust and Purchase Intention - T. Malinda; Pristiyono Pristiyono; Marlina Siregar (PT Mattawang Mediatama Solution, 2023)
Online shopping or E-Commerce is a transaction process carried out through media or intermediaries, namely in the form of online buying and selling sites or social networks that provide goods or services that are traded. Now online shopping has become a habit for some people, because of the convenience it provides. The purpose of this study was to determine the relationship between shopping experience, ease of transaction, and consumer confidence in buying interest online. In this study, the sample used was 100 samples. Samples were taken randomly or often referred to as (Probability Sampling). The analysis technique used was the SmartPLS 4.0 application, and the method used was the Structural Equation Model - Partial Least Square (SEM-PLS). Based on the results of data analysis, several conclusions can be drawn, namely the shopping experience on consumer trust is not significant but has a positive effect, so H1 is rejected. The effect of ease of transaction on consumer trust has a positive effect. Then H2 is accepted. The influence of consumer confidence on purchase intention is not significant and has a negative effect. Then H3 is rejected . The effect of shopping experience on purchase intention is not significant but has a positive effect on consumer confidence. Then H4 is rejected . The influence of ease of transaction on purchase intention is significant and has a positive effect. Then H5 is accepted. The effect of ease of transaction on consumer trust has a positive effect. Then H2 is accepted. The influence of consumer confidence on purchase intention is not significant and has a negative effect. Then H3 is rejected . The effect of shopping experience on purchase intention is not significant but has a positive effect on consumer confidence. Then H4 is rejected . The influence of ease of transaction on purchase intention is significant and has a positive effect. Then H5 is accepted. The effect of ease of transaction on consumer trust has a positive effect. Then H2 is accepted. The influence of consumer confidence on purchase intention is not significant and has a negative effect. Then H3 is rejected . The effect of shopping experience on purchase intention is not significant but has a positive effect on consumer confidence. Then H4 is rejected . The influence of ease of transaction on purchase intention is significant and has a positive effect. Then H5 is accepted. The influence of ease of transaction on purchase intention is significant and has a positive effect. Then H5 is accepted. The influence of ease of transaction on purchase intention is significant and has a positive effect. Then H5 is accepted.